Pharmacological interventions for people with borderline personality disorder - Stoffers-Winterling, Jutta M; Storebø, Ole Jakob; Pereira Ribeiro, Johanne; Kongerslev, Mickey T; Völlm, Birgit A; Mattivi, Jessica T; Faltinsen, Erlend; Todorovac, Adnan; Jørgensen, Mie S; Callesen, Henriette E; Sales, Christian P; Schaug, Julie Perrine; et al. (Cochrane database of systematic reviews, 2022)
Among people with a diagnosis of borderline personality disorder (BPD) who are engaged in clinical care, prescription rates of psychotropic medications are high, despite the fact that medication use is off-label as a treatment for BPD. Nevertheless, people with BPD often receive several psychotropic drugs at a time for sustained periods. To assess the effects of pharmacological treatment for people with BPD. For this update, we searched CENTRAL, MEDLINE, Embase, 14 other databases and four trials registers up to February 2022. We contacted researchers working in the field to ask for additional data from published and unpublished trials, and handsearched relevant journals. We did not restrict the search by year of publication, language or type of publication. Randomised controlled trials comparing pharmacological treatment to placebo, other pharmacologic treatments or a combination of pharmacologic treatments in people of all ages with a formal diagnosis of BPD. The primary outcomes were BPD symptom severity, self-harm, suicide-related outcomes, and psychosocial functioning. Secondary outcomes were individual BPD symptoms, depression, attrition and adverse events. At least two review authors independently selected trials, extracted data, assessed risk of bias using Cochrane's risk of bias tool and assessed the certainty of the evidence using the GRADE approach. We performed data analysis using Review Manager 5 and quantified the statistical reliability of the data using Trial Sequential Analysis. We included 46 randomised controlled trials (2769 participants) in this review, 45 of which were eligible for quantitative analysis and comprised 2752 participants with BPD in total. This is 18 more trials than the 2010 review on this topic. Participants were predominantly female except for one trial that included men only. The mean age ranged from 16.2 to 39.7 years across the included trials. Twenty-nine different types of medications compared to placebo or other medications were included in the analyses. Seventeen trials were funded or partially funded by the pharmaceutical industry, 10 were funded by universities or research foundations, eight received no funding, and 11 had unclear funding. For all reported effect sizes, negative effect estimates indicate beneficial effects by active medication. Compared with placebo, no difference in effects were observed on any of the primary outcomes at the end of treatment for any medication. Compared with placebo, medication may have little to no effect on BPD symptom severity, although the evidence is of very low certainty (antipsychotics: SMD -0.18, 95% confidence interval (CI) -0.45 to 0.08; 8 trials, 951 participants; antidepressants: SMD -0.27, 95% CI -0.65 to 1.18; 2 trials, 87 participants; mood stabilisers: SMD -0.07, 95% CI -0.43 to 0.57; 4 trials, 265 participants). The evidence is very uncertain about the effect of medication compared with placebo on self-harm, indicating little to no effect (antipsychotics: RR 0.66, 95% CI 0.15 to 2.84; 2 trials, 76 participants; antidepressants: MD 0.45 points on the Overt Aggression Scale-Modified-Self-Injury item (0-5 points), 95% CI -10.55 to 11.45; 1 trial, 20 participants; mood stabilisers: RR 1.08, 95% CI 0.79 to 1.48; 1 trial, 276 participants). The evidence is also very uncertain about the effect of medication compared with placebo on suicide-related outcomes, with little to no effect (antipsychotics: SMD 0.05, 95 % CI -0.18 to 0.29; 7 trials, 854 participants; antidepressants: SMD -0.26, 95% CI -1.62 to 1.09; 2 trials, 45 participants; mood stabilisers: SMD -0.36, 95% CI -1.96 to 1.25; 2 trials, 44 participants). Very low-certainty evidence shows little to no difference between medication and placebo on psychosocial functioning (antipsychotics: SMD -0.16, 95% CI -0.33 to 0.00; 7 trials, 904 participants; antidepressants: SMD -0.25, 95% CI -0.57 to 0.06; 4 trials, 161 participants; mood stabilisers: SMD -0.01, 95% CI -0.28 to 0.26; 2 trials, 214 participants). Low-certainty evidence suggests that antipsychotics may slightly reduce interpersonal problems (SMD -0.21, 95% CI -0.34 to -0.08; 8 trials, 907 participants), and that mood stabilisers may result in a reduction in this outcome (SMD -0.58, 95% CI -1.14 to -0.02; 4 trials, 300 participants). Antidepressants may have little to no effect on interpersonal problems, but the corresponding evidence is very uncertain (SMD -0.07, 95% CI -0.69 to 0.55; 2 trials, 119 participants). The evidence is very uncertain about dropout rates compared with placebo by antipsychotics (RR 1.11, 95% CI 0.89 to 1.38; 13 trials, 1216 participants). Low-certainty evidence suggests there may be no difference in dropout rates between antidepressants (RR 1.07, 95% CI 0.65 to 1.76; 6 trials, 289 participants) and mood stabilisers (RR 0.89, 95% CI 0.69 to 1.15; 9 trials, 530 participants), compared to placebo. Reporting on adverse events was poor and mostly non-standardised. The available evidence on non-serious adverse events was of very low certainty for antipsychotics (RR 1.07, 95% CI 0.90 to 1.29; 5 trials, 814 participants) and mood stabilisers (RR 0.84, 95% CI 0.70 to 1.01; 1 trial, 276 participants). For antidepressants, no data on adverse events were identified. This review included 18 more trials than the 2010 version, so larger meta-analyses with more statistical power were feasible. We found mostly very low-certainty evidence that medication may result in no difference in any primary outcome. The rest of the secondary outcomes were inconclusive. Very limited data were available for serious adverse events. The review supports the continued understanding that no pharmacological therapy seems effective in specifically treating BPD pathology. More research is needed to understand the underlying pathophysiologic mechanisms of BPD better. Also, more trials including comorbidities such as trauma-related disorders, major depression, substance use disorders, or eating disorders are needed. Additionally, more focus should be put on male and adolescent samples.